(untitled) (Cadernos de Sociomuseologia, 2022)
In this article, I bring the discussion about the category ‹‹social worker››, with which the Marxist Paulo Freire challenges us to make a choice: either we adhere to change, in the sense of our true humanization built on political action, with a view to acting collectively. towards an autonomous and emancipatory posture, or we are in favor of permanence, comfortably silent in the face of the injustices and barbarities of our time, waiting for a pre-given future, “as a mechanical repetition of the present” (Freire, 2013). In the field of museology, I discuss this Freirean category contained in the intellectual production and action of Waldisa Rússio, to which I attribute the pioneering use of the term in Brazilian museology. And I conclude that, based on Freire and Rússio, the idea of the museologist as a social worker is fully compatible with the theoretical-methodological principles of sociomuseology. Keywords: Sociomuseology; Social Worker; Paulo Freire